Measures to Increase Wild Bird Populations in Urban Areas in Java - S Van Balen (Media Konservasi, 1989)
In a previous paper on management of urban birdlife the role of nest sites was discussed (Van Balen, 1987). Attention will be paid now to what measures could be taken to improve bird habitats in relation to food availability.The sharing of some food resources often brings birds in conflict with Man. Examplesin which birds become pests are, in particular, found where monocultures, such as cereal crops offer birds an abundance of food and the opportunity to increase out of proportion. One goal of wildlife management is to control these numbers, i.e. keeping down to a harmless low level rather than eradicating, which however tends to happen with the large scale use of pesticide2 (Kalshoven, 1981). The other goal of managementis to keep bird numbers well above the dangerously low population levels with high extinction probability. In the urban environment, problems concerning the first aspect ofmanagement are rare, as most town dwelling bird species are commensals rather than parasites. In some towns of SE Asia the House Crow (Corvus splendens, gagak) can become a nuisance, as do Feral Pigeons (Columba livia, merpati) in many large European cities. In contrast, scavengers such as the Brahminy Kite (Haliastur indus, elang bondol) and the Jungle Crow (Corns macrorhynchos, gaok), formerly common in the towns of Jakarta and Semarang, where tbel used to be abundant near slaughter houses (Hoogerwerf & Siccama, 1937 - 1938), hiGe largely disappeared and are hardly found anymorein Java. This may partly be caused by drastically decreased food supplies along with improved sanitation, which already resulted in the decrease of scavenging raptors in other parts of the world (Newton, 1979). The decrease of Java Sparrows (Pad& oryzivoru, gelatik) in Singapore was said to be caused by changed local conditions, in which the supply of spced grain, food intended for poultry, etc. (on which the sparrows werelargely depend on) no longer exists (Ward, 1968); in Java the modem rice mills made rice-hulling more effective and less ,wasteful, which could have had its effect on the Javan population of the'species, which is known to have decreased dramatically during recent years (Van Helvoort, 198 1 ; Van Balen, 1984).